Flying under the radar: figurative language impairments in focal lesion patients - Ianni, Geena R.; Cardillo, Eileen R.; McQuire, Marguerite; Chatterjee, Anjan (Frontiers in Human Neuroscience, 2014)
Despite the prevalent and natural use of metaphor in everyday language, the neural basis of this powerful communication device remains poorly understood. Early studies of brain-injured patients suggested the right hemisphere plays a critical role in metaphor comprehension, but more recent patient and neuroimaging studies do not consistently support this hypothesis. One explanation for this discrepancy is the challenge in designing optimal tasks for brain-injured populations. As traditional aphasia assessments do not assess figurative language comprehension, we designed a new metaphor comprehension task to consider whether impaired metaphor processing is missed by standard clinical assessments. Stimuli consisted of 60 pairs of moderately familiar metaphors and closely matched literal sentences. Sentences were presented visually in a randomized order, followed by four adjective-noun answer choices (target + three foil types). Participants were instructed to select the phrase that best matched the meaning of the sentence. We report the performance of three focal lesion patients and a group of 12 healthy, older controls. Controls performed near ceiling in both conditions, with slightly more accurate performance on literal than metaphoric sentences. While the Western Aphasia Battery (Kertesz, 1982) and the Objects and Actions Naming Battery (Druks, 1992) indicated minimal to no language difficulty, our metaphor comprehension task indicated three different profiles of metaphor comprehension impairment in the patients’ performance. Single case statistics revealed comparable impairment on metaphoric and literal sentences, disproportionately greater impairment on metaphors than literal sentences, and selective impairment on metaphors. We conclude our task reveals that patients can have selective metaphor comprehension deficits. These deficits are not captured by traditional neuropsychological language assessments, suggesting overlooked communication difficulties.